Kelimpahan Lalat Buah (Bactrocera spp.) pada macam Klon Pohon Jeruk dI Kabupaten Sleman - Salwa Ramadina Putri Utari Utari; Muamar Kadafi Kadafi; Fahmi Dwilaksono Dwilaksono; Ayu Purnamasari Purnamasari; Alfassabiq Khairi Khairi (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Fruit flies (Bactrocera spp.) are among the most serious pests in citrus production due to their high infestation potential and detrimental effects on fruit quality. This study examined fruit fly abundance based on sex and citrus tree clones and evaluated the impact of trap placement position on fruit fly populations in Sleman Regency, Indonesia. The experiment was conducted in August 2025 at Pusat Inovasi Agroteknologi, Universitas Gadjah Mada, employing a Completely Randomized Block Design with four trap placement treatments: medium inside, high inside, medium outside, and high outside. Medium and high trap heights were set at 1 m and 2 m above ground level, respectively, with traps positioned either inside or outside the tree canopy. Observations were performed at two-day intervals over 15 observation periods on three citrus species: Siamese orange (Citrus nobilis Lour.), kaffir lime (Citrus hystrix), and grapefruit (Citrus maxima (Burm.) Merr.). The results showed that fruit fly abundance was consistently higher in traps installed outside the tree canopy than in those placed inside across all citrus species and observation periods. No significant differences were detected between medium and high trap heights within the same placement location. Female fruit flies exhibited greater population variability than males, indicating higher sensitivity to environmental factors. Furthermore, correlation analysis revealed strong positive relationships among citrus clones, suggesting similar levels of susceptibility to fruit fly infestation. In conclusion, the findings highlight that trap placement location plays a more decisive role than trap height in influencing fruit fly abundance on citrus trees.